The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1991
DOI: 10.1073/pnas.88.6.2545
|View full text |Cite
|
Sign up to set email alerts
|

Development of a possible nonmammalian test system for radiation-induced germ-cell mutagenesis using a fish, the Japanese medaka (Oryzias latipes).

Abstract: To develop a specific-locus test (SLT) system for environmental mutagenesis using vertebrate species other than the mouse, we first established a tester stock of the fish medaka (Oryzias latipes) that is homozygous recessive at three loci. The phenotypic expression of these loci can be easily recognized early in embryonic development by observation through the transparent egg membrane. We irradiated wildtype males with '"Cs -rays to determine the dose-response relationships for dominant lethal and specific-loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(37 citation statements)
references
References 21 publications
1
36
0
Order By: Relevance
“…1) to the potent germ cell mutagen, ethyl-N-nitrosourea (ENU), for 1 hr on 2 consecutive days and bred with multiple untreated, wild-type females (8-10 females/males, 6-10 weeks of age) for either 6 days following treatment, or >60 days post-treatment, to collect offspring derived from postmeiotic germ cells (spermatozoa, late spermatids), or from spermatogonial stem cells, respectively, exposed to the mutagen [Shima and Shimada, 1991]. Progeny were hemizygous for the k bacteriophage containing the cII target gene contributed only by the male parent.…”
Section: Mutagen Treatmentmentioning
confidence: 99%
“…1) to the potent germ cell mutagen, ethyl-N-nitrosourea (ENU), for 1 hr on 2 consecutive days and bred with multiple untreated, wild-type females (8-10 females/males, 6-10 weeks of age) for either 6 days following treatment, or >60 days post-treatment, to collect offspring derived from postmeiotic germ cells (spermatozoa, late spermatids), or from spermatogonial stem cells, respectively, exposed to the mutagen [Shima and Shimada, 1991]. Progeny were hemizygous for the k bacteriophage containing the cII target gene contributed only by the male parent.…”
Section: Mutagen Treatmentmentioning
confidence: 99%
“…With the reservation that we then had detected only one spontaneous viable mutation, we concluded that the quantitative data, including the doubling doses for dominant lethal and viable mutation obtained from the medaka SLT, are quite comparable to those from the mouse SLT and, hence, indicated the validity of the medaka SLT as a possible nonmammalian test system for studying germ-cell mutagenesis. In addition, we noted that because the spontaneous and radiationinduced "total mutation" frequencies are almost one order of magnitude higher than those for the "viable mutation," the doubling dose for total mutations, i.e., the amount of radiation needed to double the natural incidence that can be operationally calculated by dividing the spontaneous incidence by the induced rate per unit dose, appeared to be almost the same as those for dominant lethal and viable mutations (Shima and Shimada, 1991). Therefore, we concluded that although total mutation was a unique genetic end point proposed on the basis of recognizing the mutant phenotypes during the embryonic development of an oviparous vertebrate, this end point could be used as a quantitatively feasible genetic end point in a study of mutagenesis.…”
Section: Development Of a Nonmammalian Specific-locus Test System Usimentioning
confidence: 94%
“…Table 1 shows the number of embryos and genetic loci scored up to May 9, 2000 (1,091,824 embryos corresponding to 3,135,999 loci). For details, see Shima and Shimada (1991) and Shimada and Shima (1998).…”
Section: Development Of a Nonmammalian Specific-locus Test System Usimentioning
confidence: 98%
“…In 1975, Tomita reported the first spontaneous medaka mutant collection (35). These studies with medaka mutants complement the zebrafish data and genetic screens in medaka (36,37) have provided important additional information that will be useful in understanding human diseases.…”
Section: Zebrafish and Medakamentioning
confidence: 99%